Lessons Learned From Developing a MCI Virtual Empowerment Program?. Issue 1 (June 2021) - Bradley Fain, W.; Nare, Megan; Doiron, Matthew; Farmer, Sarah; Johnson, Jeremy; Laforce, Salimah; Ramesh, Aparna; Rodriguez, Amy; Vickers, Kayci; Zubatiy, Tamara; Mynatt, Elizabeth
In the Spring of 2020, COVID-19 closures and safe distancing orders required healthcare programs across the US to cease in-person treatment. This paper presents a case study of rapidly pivoting a novel, 12-month comprehensive clinical lifestyle program combining education, occupational therapy, cognitive training, and social interaction to an online application-based education program. The focus of the program is empowerment research for people newly diagnosed with mild cognitive impairment (MCI) and their care partners, and is conducted by the Emory Brain Health Center. Georgia Tech developed an education application (named MyCEP) for use with our MCI and care partner population combining off-the-shelf services and customized user interfaces. We used an iterative design and development process, testing our application with our end users and our treatment providers, and made updates based on our discovery of the need for new capabilities and requirements. We present the discovery of emergent practices by family members and healthcare providers to meet the new requirements for successful virtual engagement.